A comparison of bran from parboiled and raw rice : nutrient content and aflatoxin production - INDIRA KALYANASUNDRAM*, P. JAYARAMAN and (Indian Phytopathology, 2002)
A comparative analysis of proteins, Jipids, total nitrogen and thiamine content of samples of parboiled and raw rice bran showed that total nitrogen and buffer soluble proteins were higher in raw rice (rr) bran, while lipids and thiamine were higher in parboiled rice (pbr) bran. The ability to support aflatoxin production in the two types of bran, when assessed using a toxigenic Aspergillus parasiticus strain (NRRL 2999), showed pbr bran to support higher aflatoxin production than rr bran. This was in contrast to the lower ATBl levels observed in pbr bran in nature.